2011
DOI: 10.1007/s00534-011-0415-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the silk protein sericin on cryopreserved rat islets

Abstract: The present results showed that serum-free medium containing sericin is useful for both cryopreservation and cell culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 19 publications
0
27
0
1
Order By: Relevance
“…Most studies to date have not found sericin superior to FBS in cryopreservative experiments. 21,22,33 One exception where a freezing medium containing sericin performed better than a medium with FBS was a study using Chinese-hamster ovary cells frozen in PBS, supplemented with 1% sericin, 0.5% maltose, 0.3% proline, 0.3% glutamine, and 10% DMSO. 18 Thus, our results are in agreement with the majority of data published thus far.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies to date have not found sericin superior to FBS in cryopreservative experiments. 21,22,33 One exception where a freezing medium containing sericin performed better than a medium with FBS was a study using Chinese-hamster ovary cells frozen in PBS, supplemented with 1% sericin, 0.5% maltose, 0.3% proline, 0.3% glutamine, and 10% DMSO. 18 Thus, our results are in agreement with the majority of data published thus far.…”
Section: Discussionmentioning
confidence: 99%
“…It has successfully improved the survival of various cell cultures during cryopreservation when used as a protein in the freezing medium (Terada et al 2002;Sasaki et al 2005). As proteins have a lower toxicity than DMSO and are also thought to act as a cell membrane-impermeable cryoprotectant and have an inhibitory effect against the ice crystals formation, sericin as a cell membrane-impermeable cryoprotectant may thus protect cells from cryo-injury (Ohnishi et al 2011).…”
Section: Sds-polyacrylamide Gel Electrophoresis (Sds-page)mentioning
confidence: 99%
“…Among its wide range of physiological functions, sericin has been reported to ameliorate constipation (Sasaki et al, 2000a), suppress colorectal cancer (Sasaki et al, 2000b;Zhaorigetu et al, 2001;Zhaorigetu et al, 2007), suppress skin cancer (Zhaorigetu et al, 2003b), and apply cell activating/cytoprotective properties (Terada et al, 2002;Terada et al, 2005;Ohnishi et al, 2012) and adiponectin-increasing/promoting effects (Okazaki et al, 2010). In addition, supplements exerting physiological effects have been put to practical use.…”
Section: Introductionmentioning
confidence: 99%